Аналіз електрокардіографічних показників у єдиноборців залежно від спортивної кваліфікації - Михалюк, Євген Леонідович; Гуніна, Л. М.; Кузьменко, М. В.; Михалюк, Е. Л.; Гунина, Л. М.; Mikhalyuk, E. L.; Gunina, L. M.; Kuzmenko, M. V. (Чорноморський національний університет ім. Петра Могили, 2018)
Метою роботи був аналізу встановлених змін електрокардіографічних показників у єдиноборців залежно від спортивної кваліфікації. Після проведеного скринінгу 6224 електрокардіограм виділена група спортсменів, які займаються контактними єдиноборствами – 462 особи, в тому числі 255 боксерів, 127 кікбоксерів і 80 тхеквондистів. Електрокардіографічні характеристики боксерів кваліфікації «майстер спорту України ‒ майстер спорту міжнародного класу» відрізняються від менш кваліфікованих боксерів меншим числом випадків дихальної аритмії та тахікардії (вище 80 уд./хв.), і, навпаки, більшим числом осіб з брадикардією і змінами на ЕКГ за рахунок наявності синдрому ранньої реполяризації шлуночків і міграції водія ритму. У кікбоксерів з кваліфікацією «майстер спорту України ‒ майстер спорту міжнародного класу» частіше зустрічається брадикардія, рідше ‒ дихальна аритмія і частота серцевих скорочень в межах 61-79 уд./хв., при цьому відсутні достовірні відмінності щодо змін на ЕКГ. Серед тхеквондистів кваліфікації «майстер спорту України ‒ майстер спорту міжнародного класу» частіше зустрічається брадикардія, меншою є кількість осіб з частотою серцевих скорочень в межах 61-79 уд./хв., і відсутні відмінності щодо змін на ЕКГ порівняно з тхеквондистами кваліфікації «І розряд ‒ кандидат в майстри спорту України». Після фізичного навантаження у вигляді субмаксимального тесту PWC170 у всіх спортсменів з AV-блокадою 1 ступеня або нижньопередсердним ритмом та міграцією водія ритму відбулося відновлення синусового ритму. У спортсменів з синдромами CLC та неповною блокадою передньої гілки лівої ніжки пучка Гіса за даними ехокардіографії не виявлено дилатації та гіпертрофії серця, а наявність синдрому ранньої реполяризації шлуночків та неповної блокади правої ніжки пучка Гіса слід розглядати як особливості ЕКГ у цієї категорії спортсменів. Резюме. Целью работы было проведение анализа электрокардиографических показателей у единоборцев в зависимости от спортивной квалификации. После проведенного скрининга 6224 электрокардиограмм выделена группа спортсменов, занимающихся контактными единоборствами – 462 человека, в том числе 255 боксеров, 127 кикбоксеров и 80 тхэквондистов. Боксеры уровня мастер спорта – мастер спорта международного класса отличаются от менее квалифицированных боксеров меньшим числом лиц с дыхательной аритмией, меньшим количеством спортсменов с частотой сердечных сокращений более 80 уд / мин, большим числом лиц с брадикардией и с изменениями на ЭКГ за счет синдрома ранней реполяризации желудочков и миграции водителя ритма. У кикбоксеров уровня мастер спорта – мастер спорта международного класса чаще встречается брадикардия, реже дыхательная аритмия и частота сердечных сокращений в пределах 61-79 уд./мин, При этом отсутствуют достоверные различия по изменениям на ЭКГ. Среди тхэквондистов квалификации «мастер спорта Украины – мастер спорта международного класса» чаще встречается брадикардия, меньше лиц с частотой сердечных сокращений в пределах 61-79 уд./мин и отсутствуют различия по изменениям на ЭКГ по сравнению с тхэквондистами квалификации «I разряд ‒ кандидат в мастера спорта Украины». После физической нагрузки в виде субмаксимального теста PWC170 у всех спортсменов с AV-блокадой 1 степени, или нижнепредсердным ритмом и миграцией водителя ритма произошло восстановление синусового ритма. У спортсменов с синдромами CLC и неполной блокады передней ветви левой ножки пучка Гиса по данным эхокардиографии не обнаружены дилатация и гипертрофия сердца, а наличие синдрома ранней реполяризации желудочков и неполной блокады правой ножки пучка Гиса следует рассматривать как особенности ЭКГ в этой категории спортсменов. Abstract. Increasing the effectiveness of athletes training process is impossible without improving the system of assessing the functional state of their cardiovascular system. Experts in the field of sports medicine with the help of electrocardiography proved that the cardiovascular system is the most responsive system to changes in both the external and internal environment. The purpose of the study was the analysis of the results of changes in electrocardiographic parameters in single combaters depending on the growth of their sports skills. Material and methods. We analyzed 6224 electrocardiograms of athletes of qualification from the youth category to the honored masters of sports of both sexes, aged from 5 to 40 years. The total number of surveyed individuals was thoroughly studied and the following sports were selected: martial arts – 462 athletes, boxing – 255 sportsmen, kickboxing – 127 sportsmen, and taekwondo – 80 athletes who were surveyed during the preparatory period of the training process. Results and discussion. Athletes with an AV-blockade of the 1st degree, anesthetic rhythm and rhythm driver migration on a bicycle test performed a submaximal PWC170 test. Athletes with CLC syndromes and incomplete blockade of the right hip leg underwent the procedure of echocardiography. For reliable information on the effect of specific physical activity on the bioelectric activity of myocardium monoliths, it is expedient to conduct an analysis of the results obtained separately for each particular sport (boxing, kickboxing, taekwondo), taking into account sports qualification. Boxers of the level MS-MSIC differ from less skilled boxers by fewer people with respiratory arrhythmia, fewer athletes with heart rate more than 80 beats/min, more people with bradycardia and with changes in ECG due to SEVR and migration of driver of rhythm. In kickboxers of the level MS-MSIC, bradycardia is more common, respiratory arrhythmia and heart rate are rarer in the range of 61-79 beats/min, with no significant differences with regard to ECG changes. Among taekwondo sportsmen of the level MS-MSIC bradycardia is more common, there are fewer people with heart rate within 61-79 beats/min and there are no differences regarding ECG changes in comparison with the taekwondo sportsmen of the level CMS-1 qualification. Conclusions. After physical activity in the form of a submaximal test PWC170, all athletes with AV-blockade of the 1st degree, or atherosclerotic rhythm and migratory rhythm driver, recovered sinus rhythm. Athletes with CLC and ILBBBG syndromes did not find dilatation and hypertrophy of the heart according to echocardiography data, and the presence of SEVR and IRBBB should be considered as features of the ECG in this category of athletes.
Анализ электрокардиографических показателей единоборцев в зависимости от спортивной квалификации
Analysis of Electrocardiographic Indicators in Combating Sportsmen Depending on their Sports Qualification
Keywords: кваліфіковані єдиноборці; бокс; кікбоксинг; тхеквондо; електрокардіограма; серцевий ритм; синдром ранньої реполяризації шлуночків; кикбоксинг; электрокардиограмма; синдромы CLC; неполная блокада передней ветви левой ножки пучка Гиса; синдром ранней реполяризации желудочков; неполная блокада правой ножки пучка Гиса; AV-блокада 1 степени; нижнепредсердный ритм; миграция водителя ритма; спортсмены единоборцы; skilled athletes single combat; boxing; kickboxing; taekwondo; electrocardiogram; heart rate; cardiac rhythm; syndrome of early ventricular repolarization